1997
DOI: 10.1007/bf02106226
|View full text |Cite
|
Sign up to set email alerts
|

Inter-examiner variability of Transcranial Doppler procedure and reports: a multicenter survey

Abstract: The application of the same criteria in different laboratories may facilitate the standardization of TCD examinations and support the reproducibility of clinical reports based on TCD parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The main reasons for delayed accreditation were incomplete studies attributable to missing Doppler waveforms and images (33.0%), inconsistencies between the reported artery stenosis and the lab's defined diagnostic criteria for stenosis (23.7%), and discrepancies between the final results and images (17.5%). These findings underscore reports in the literature that TCD procedures are complicated and highly operator dependent, for both technical performance and subsequent interpretation . Our study also demonstrated that most physicians interpreting TCD studies had limited formal instruction.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The main reasons for delayed accreditation were incomplete studies attributable to missing Doppler waveforms and images (33.0%), inconsistencies between the reported artery stenosis and the lab's defined diagnostic criteria for stenosis (23.7%), and discrepancies between the final results and images (17.5%). These findings underscore reports in the literature that TCD procedures are complicated and highly operator dependent, for both technical performance and subsequent interpretation . Our study also demonstrated that most physicians interpreting TCD studies had limited formal instruction.…”
Section: Discussionsupporting
confidence: 77%
“…These findings underscore reports in the literature that TCD procedures are complicated and highly operator dependent, for both technical performance and subsequent interpretation. 23,24 Our study also demonstrated that most physicians interpreting TCD studies had limited formal instruction. The established practice qualification pathway requires physicians to have 3 years' experience with interpretation of at least 300 TCD studies.…”
Section: Discussionmentioning
confidence: 59%
“…Although TCD is not a direct method and indirectly measures only global CBF, its relatively noninvasive nature makes it suitable as a bedside measurement and perhaps makes it a more clinically applicable test. Finally, interoperator variability is low with TCD when the operators are experienced in use of the technology (27,28). In this study, all TCD measurements were performed by the same investigator, who was experienced in the use of TCD.…”
Section: Figurementioning
confidence: 98%
“…TCD fulfills many of these criteria but TCD measurements are significantly operator-dependent and can have a wide interexaminer variability. 239 Transcranial color-coded sonography has the advantage of visualization of tissues and reducing sampling error but comes with increased cost and training of the sonographer. 240 TCD monitoring of CA and CVR can also be affected by patient position making day-to-day trending of these variables potentially troublesome.…”
Section: Chronic Central Nervous System Diseasesunderstanding Pathobimentioning
confidence: 99%